A UPVC material with high rigidity and high impact resistance and its preparation method and application
By optimizing the PVC pipe formula and using PVC/ABS/MBS co-mixed gold and other additives, high-stiffness and high impact resistance UPVC materials were prepared, which solved the problem of insufficient strength and stiffness of existing polymer alloy cable trays and significantly improved the mechanical properties of the material.
Patent Information
- Application Number
- CN202310292074.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-03-23
AI Technical Summary
The existing polymer alloy cable tray products have low strength and stiffness, which is difficult to meet the requirements of engineering large span bridges. In addition, the low-temperature toughness and impact resistance of pure polyvinyl chloride polymer bridges in low temperature environments are poor.
By optimizing the formulation raw materials of ordinary PVC pipes, using PVC/ABS/MBS co-mixed gold as the matrix resin, and adding fillers, heat stabilizers, processing aids, lubricants and titanium dioxide, UPVC materials with high stiffness, high impact resistance, good toughness and processing properties are prepared.
The stiffness and impact resistance of UPVC materials have been significantly improved, with an elastic modulus of 6048.85Pa and an impact resistance strength of 51.33J/m2, which is better than traditional PVC materials and has good practical application value.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a UPVC material with high rigidity and high impact resistance, and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Single PVC resin material has the disadvantages of poor thermal stability, poor impact toughness, and low rigidity, so the research on plastic materials using polymer alloys as raw materials came into being. In the production process of polymer cable tray products, polymer alloy UPVC material is another new model of "plastic replacing steel" in electrical engineering applications after polyvinyl chloride resin flame-retardant cable troughs. It combines the flame retardant, acid-resistant, alkali-resistant and good physical and chemical properties of polymer materials, and through the organic dissolution of its special polymer materials and functional additives containing other characteristics, it has high rigidity and high impact resistance, becoming a polymer alloy material product that meets various application occasions. It is energy-saving and environmentally friendly, in line with the concept of human environment, and is made of polymer alloy technology. It has excellent performance and cost-effectiveness, and is now recognized and applied in various fields and industries.
[0004] However, the inventors found that the strength and rigidity of existing polymer alloy cable tray products are still relatively low, making it difficult to meet the requirements of large-span cable trays in engineering projects; and the low-temperature toughness and impact resistance of pure polyvinyl chloride polymer cable trays are poor, making them difficult to use in outdoor low-temperature environments for a long time. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, the present invention proposes a UPVC plastic alloy with high rigidity and high impact resistance and its preparation method and application, which are used in the field of electrical engineering such as polymer cable trays. The present invention successfully prepares a UPVC material with high rigidity, high impact resistance, good toughness and processing performance by optimizing the formula raw materials of ordinary PVC pipes, which has good practical application value in electrical engineering.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a UPVC material with high rigidity and high impact resistance, comprising the following raw materials in parts by weight:
[0008] 100 parts of PVC resin, 10-20 parts of ABS resin, 2-10 parts of MBS resin, 100-150 parts of filler, 5-10 parts of heat stabilizer, 5-15 parts of processing aid, 1-3 parts of lubricant, and 0.5-1.5 parts of titanium dioxide.
[0009] The mixing, extrusion process and process parameters of polymer materials have a great influence on the mechanical properties of UPVC materials. Therefore, in a second aspect of the present invention, a method for preparing the above-mentioned UPVC material with high rigidity and high impact resistance is provided, and the preparation method comprises the following steps:
[0010] Step 1: Weigh each component raw material as required;
[0011] Step 2: Add the raw materials of each component into the mixer, heat it up, then cool it and discharge it;
[0012] Step 3: The mixed material obtained in step 2 is processed and formed by extrusion process.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The above technical solution provides a method for preparing a UPVC material with high rigidity and high impact resistance. The present invention successfully prepares a UPVC material with high rigidity and high impact resistance according to an advanced preparation process by blending three polymer plastics, PVC, ABS and MBS, and further optimizing the types, amounts and proportions of other additives. The UPVC material has good application in the field of electrical engineering, such as polymer cable trays. The elastic modulus is tested according to GB / T1040-92, and the performance index is 6048.85Pa, while the traditional PVC cable tray is about 4500Pa; the impact strength is tested according to GB / T 1843-2008, and the performance index is 51.33J / m 2 , traditional PVC material is 40J / m 2 Compared with traditional PVC materials, the rigidity and impact resistance of the high-rigidity and high-impact UPVC prepared by the present invention are significantly improved, and therefore has good practical application value. DETAILED DESCRIPTION
[0015] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0016] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0017] The present invention is further described in conjunction with specific examples. The following examples are only for explaining the present invention and are not intended to limit the content thereof. If the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or the conditions recommended by the reagent company; the reagents and consumables used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0018] As mentioned above, the existing PVC polymer bridge products have low rigidity and cannot meet the market demand for large-span bridges. They are also very brittle and cannot absorb enough impact energy when subjected to instantaneous impact, resulting in a significant shortcoming in toughness. At the same time, during the processing, the polymer material itself has poor processing performance and the alloy material system has phase interface differentiation problems, which further increases the processing difficulty and limits the further development of polymer alloy bridges.
[0019] In view of this, the present invention provides a UPVC material with high rigidity and high impact resistance, which is made of the following raw materials in parts by mass:
[0020] 100 parts of PVC resin, 10-20 parts of ABS resin, 2-10 parts of MBS resin, 100-150 parts of filler, 5-10 parts of heat stabilizer, 5-15 parts of processing aid, 1-3 parts of lubricant, and 0.5-1.5 parts of titanium dioxide.
[0021] PVC / ABS / MBS alloy is used as the base resin. ABS resin has excellent chemical stability, oil resistance, certain rigidity and hardness, and excellent comprehensive physical and mechanical properties; MBS resin, as one of the most important impact modifiers of PVC, can greatly improve the toughness of the product, but it should be noted that the dosage should not be too large, otherwise it will affect the rigidity of the UPVC.
[0022] In a specific embodiment of the present invention, the filler can be kaolin, diatomaceous earth, carbon black, alumina powder and calcium carbonate, preferably calcium carbonate, and further, the calcium carbonate is light activated calcium carbonate. The addition of calcium carbonate filler can enhance the rigidity and strength of UPVC material, which is manifested as the improvement of mechanical properties. At the same time, its low price can reduce production costs.
[0023] In one embodiment of the present invention, the heat stabilizer is a lead salt stabilizer or a composite calcium zinc stabilizer, preferably a composite calcium zinc stabilizer. The composite calcium zinc stabilizer can improve the thermal stability of UPVC, reduce its thermal decomposition temperature, and improve the processing technology.
[0024] In a specific embodiment of the present invention, the processing aid is one or a combination of ACR processing aid or CPE processing aid, and preferably, the impact modifier is ACR processing aid. ACR can induce a large number of silver streaks to form shear bands, thereby consuming a large amount of energy, thereby significantly improving the impact properties of rigid PVC materials at room temperature and low temperature, and promoting the plasticization and gelation of PVC resin.
[0025] In a specific embodiment of the present invention, the lubricant is any one or more of stearic acid, microcrystalline wax, PE wax and monoglyceride; preferably, the lubricant is a combination of stearic acid, microcrystalline wax, PE wax and monoglyceride, and further preferably, the mass ratio of stearic acid, microcrystalline wax, PE wax and monoglyceride is 1-3:0.1-1:0.1-2:2-3.
[0026] The present invention successfully prepares a UPVC material with high rigidity and high impact resistance by blending three polymer plastics, PVC, ABS and MBS, and further optimizing the types, dosages and proportions of other additives according to an advanced preparation process, and has good applications in the field of electrical engineering, such as the field of polymer cable trays. Compared with traditional PVC materials, the UPVC with high rigidity and high impact resistance prepared by the present invention has significantly improved rigidity and impact resistance, and has achieved reinforcement and toughening at the same time, and has good practical application value.
[0027] In a specific embodiment of the present invention, the UPVC material with high rigidity and high impact resistance has the following components in parts by weight:
[0028] 100 parts of PVC resin by weight, 10 parts of ABS resin, 10 parts of MBS resin, 140 parts of light activated calcium carbonate, 8 parts of composite calcium zinc stabilizer, 10 parts of ACR processing aid, 1 part of stearic acid, 1 part of PE wax, 1.15 parts of titanium dioxide; or,
[0029] 100 parts of PVC resin, 15 parts of ABS resin, 5 parts of MBS resin, 150 parts of light activated calcium carbonate, 8 parts of composite calcium zinc stabilizer, 10 parts of ACR processing aid, 2 parts of stearic acid, 2 parts of PE wax, and 1.15 parts of titanium dioxide.
[0030] The mixing order of polymer materials and the control setting of mixing parameters are particularly important, which will further affect the plasticity of the raw materials in the subsequent processing. At the same time, the subsequent extrusion process will also affect the plasticization effect of the final product. Therefore, in one specific embodiment of the present invention, a preparation method of the above-mentioned UPVC material with high rigidity and high impact resistance is provided, and the preparation method comprises the following steps:
[0031] Step 1: Weigh each component raw material as required;
[0032] Step 2: Add the raw materials of each component into the mixer, heat it up, then cool it and discharge it;
[0033] Step 3: The mixed material obtained in step 2 is processed and formed by extrusion process.
[0034] In a specific embodiment of the present invention, in the step 2, the temperature is raised to 120-150° C., and then cooled down; when cooled to 20-60° C., the material is discharged;
[0035] In a specific embodiment of the present invention, in step 3, the extrusion process is performed using a twin-screw extrusion process, which specifically includes:
[0036] Step 3-1: the extruder controls the temperature to 100-130°C and maintains the preheating temperature;
[0037] Step 3-2: Heat the barrel to 150-230°C, adjust the parameters, extrude the raw material mixture, and pull it into shape.
[0038] In one specific embodiment of the present invention, in step 3-1, the preheating temperature is maintained for 30-120 minutes;
[0039] In the step 3-2, the parameters are controlled as follows: the current is controlled at 10A-30A, the extrusion speed is controlled at 5-20r / min, the feeding speed is controlled at 5-20r / min, the vacuum degree of the host is controlled below -0.02mpa, and the mold temperature is controlled at 150-230°C;
[0040] In the step 3-2, in the traction molding section, the traction speed is controlled at 0.5-1.5 m / s, and the molding vacuum degree is controlled below -0.02 MPa (including -0.02 MPa).
[0041] In a specific embodiment of the present invention, the application of the above-mentioned UPVC material with high rigidity and high impact resistance in the field of electrical engineering is provided, such as polymer cable tray.
[0042] The present invention is further explained by the following examples, but it does not constitute a limitation of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The test methods for the following examples are generally carried out under normal conditions.
[0043] Example 1
[0044] A UPVC plastic with high rigidity and high impact resistance is composed of 100 parts by weight of PVC resin, 10 parts by weight of ABS resin, 10 parts by weight of MBS resin, 140 parts by weight of light activated calcium carbonate, 8 parts by weight of composite calcium zinc stabilizer, 10 parts by weight of ACR processing aid, 1 part by weight of stearic acid, 1 part by weight of PE wax, and 1.15 parts by weight of titanium dioxide.
[0045] The mixing process and parameter settings are as follows:
[0046] 1) Add the weighed raw materials into the working mixer;
[0047] 2) Cooling when the mixture temperature reaches 120°C;
[0048] 3) Discharge the material when cooled to 45°C;
[0049] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0050] l) The experimental extruder is preheated to a temperature of 130°C;
[0051] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0052] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0053] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 6034.63Pa and the impact strength is 51.33J / m 2 .
[0054] Example 2
[0055] A UPVC material with high rigidity and high impact resistance is composed of 100 parts by weight of PVC resin, 15 parts of ABS resin, 5 parts of MBS resin, 150 parts of light activated calcium carbonate, 8 parts of composite calcium zinc stabilizer, 10 parts of ACR processing aid, 2 parts of stearic acid, 2 parts of PE wax, and 1.15 parts of titanium dioxide.
[0056] The mixing process and parameter settings are as follows:
[0057] 1) Add the weighed raw materials into the working mixer;
[0058] 2) Cooling when the mixture temperature reaches 120°C;
[0059] 3) Discharge the material when cooled to 45°C;
[0060] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0061] l) The experimental extruder is preheated to a temperature of 130°C;
[0062] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0063] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0064] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 6048.85Pa and the impact strength is 50.82J / m 2 .
[0065] Comparative Example 1
[0066] A UPVC material with high rigidity and high impact resistance, which differs from Example 1 in that: the weight of PVC resin is 100 parts, light activated calcium carbonate is 140 parts, composite calcium zinc stabilizer is 8 parts, ACR processing aid is 10 parts, stearic acid is 1 part, PE wax is 1 part, and titanium dioxide is 1.15 parts.
[0067] The mixing process and parameter settings are as follows:
[0068] 1) Add the weighed raw materials into the working mixer;
[0069] 2) Cooling when the mixture temperature reaches 120°C;
[0070] 3) Discharge the material when cooled to 45°C;
[0071] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0072] l) The experimental extruder is preheated to a temperature of 130°C;
[0073] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0074] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0075] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 4489.76Pa and the impact strength is 40.61J / m 2 .
[0076] Comparative Example 2
[0077] A UPVC material with high rigidity and high impact resistance, which is different from Example 1 in that: 100 parts by weight of PVC resin, 150 parts of light activated calcium carbonate, 8 parts of composite calcium zinc stabilizer, 10 parts of ACR processing aid, 2 parts of stearic acid, 2 parts of PE wax, and 1.15 parts of titanium dioxide are used as the mixing process and parameter settings are as follows:
[0078] 1) Add the weighed raw materials into the working mixer;
[0079] 2) Cooling when the mixture temperature reaches 120°C;
[0080] 3) Discharge the material when cooled to 45°C;
[0081] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0082] l) The experimental extruder is preheated to a temperature of 130°C;
[0083] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0084] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0085] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 4578.39Pa and the impact strength is 38.80J / m 2 .
[0086] Comparative Example 3
[0087] A UPVC material with high rigidity and high impact resistance, which differs from Example 1 in that: 100 parts by weight of PVC resin, 10 parts by weight of ABS resin, 140 parts by weight of light activated calcium carbonate, 8 parts by weight of composite calcium zinc stabilizer, 10 parts by weight of ACR processing aid, 1 part by weight of stearic acid, 1 part by weight of PE wax, and 1.15 parts by weight of titanium dioxide.
[0088] The mixing process and parameter settings are as follows:
[0089] 1) Add the weighed raw materials into the working mixer;
[0090] 2) Cooling when the mixture temperature reaches 120°C;
[0091] 3) Discharge the material when cooled to 45°C;
[0092] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0093] l) The experimental extruder is preheated to a temperature of 130°C;
[0094] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0095] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0096] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 5879.66Pa and the impact strength is 32.19J / m 2 .
[0097] Comparative Example 4
[0098] A UPVC material with high rigidity and high impact resistance, which differs from Example 1 in that: the weight of PVC resin is 100 parts of the base, MBS resin is 10 parts, light activated calcium carbonate is 140 parts, composite calcium zinc stabilizer is 8 parts, ACR processing aid is 10 parts, stearic acid is 1 part, PE wax is 1 part, and titanium dioxide is 1.15 parts.
[0099] The mixing process and parameter settings are as follows:
[0100] 1) Add the weighed raw materials into the working mixer;
[0101] 2) Cooling when the mixture temperature reaches 120°C;
[0102] 3) Discharge the material when cooled to 45°C;
[0103] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0104] l) The experimental extruder is preheated to a temperature of 130°C;
[0105] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0106] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0107] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 4783.70Pa and the impact strength is 48.34J / m 2 .
[0108] Comparative Example 5
[0109] A UPVC material with high rigidity and high impact resistance, which differs from Example 1 in that: the weight of PVC resin is 100 parts of the base, MBS resin is 20 parts, light activated calcium carbonate is 140 parts, composite calcium zinc stabilizer is 8 parts, ACR processing aid is 10 parts, stearic acid is 1 part, PE wax is 1 part, and titanium dioxide is 1.15 parts.
[0110] The mixing process and parameter settings are as follows:
[0111] 1) Add the weighed raw materials into the working mixer;
[0112] 2) Cooling when the mixture temperature reaches 120°C;
[0113] 3) Discharge the material when cooled to 45°C;
[0114] The obtained mixed material is processed and formed by extrusion process, and the twin-screw extrusion process is:
[0115] l) The experimental extruder is preheated to a temperature of 130°C;
[0116] 2) After the temperature reaches the constant temperature for 30 minutes, the barrel temperature is heated to 180°C and extrusion begins;
[0117] 3) The extruder current is controlled at 25A, the extrusion speed is controlled at 8r / min, the feeding speed is controlled at 6r / min, the host is controlled at -0.08mpa, and the mold temperature is controlled at 180℃;
[0118] 4) In the traction molding section, the traction speed is controlled at 0.5m / s and the molding vacuum is controlled at -0.08mpa. The elastic modulus of the obtained product is 4115.19Pa and the impact strength is 58.92J / m 2 It can be seen that the elastic modulus decreases significantly when the amount of MBS resin is too much.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A UPVC material with high rigidity and high impact resistance, characterized in that: It is made of the following raw materials in parts by weight: 100 parts of PVC resin, 10-20 parts of ABS resin, 2-10 parts of MBS resin, 100-150 parts of filler, 5-10 parts of heat stabilizer, 5-15 parts of processing aid, 1-3 parts of lubricant, 0.5-1.5 parts of titanium dioxide; The filler is calcium carbonate; The method for preparing the UPVC material with high rigidity and high impact resistance comprises the following steps: Step 1: Weigh each component raw material as required; Step 2: Add the raw materials of each component into the mixer, heat it up, then cool it and discharge it; Step 3: The mixed material obtained in step 2 is processed and formed by extrusion process.
2. The UPVC material with high rigidity and high impact resistance according to claim 1, characterized in that: The calcium carbonate is light activated calcium carbonate.
3. The UPVC material with high rigidity and high impact resistance according to claim 1, characterized in that: The heat stabilizer is a lead salt stabilizer or a composite calcium zinc stabilizer.
4. The UPVC material with high rigidity and high impact resistance according to claim 3, characterized in that: The heat stabilizer is a composite calcium zinc stabilizer.
5. The UPVC material with high rigidity and high impact resistance according to claim 1, characterized in that: The processing aid is one of ACR processing aid and CPE processing aid, or a combination of the two.
6. The UPVC material with high rigidity and high impact resistance according to claim 5, characterized in that: The processing aid is ACR processing aid.
7. The UPVC material with high rigidity and high impact resistance according to claim 1, characterized in that: The lubricant is any one or more of stearic acid, microcrystalline wax, PE wax and monoglyceride.
8. The UPVC material with high rigidity and high impact resistance according to claim 7, characterized in that: The lubricant is a combination of stearic acid, microcrystalline wax, PE wax and monoglyceride.
9. The UPVC material with high rigidity and high impact resistance according to claim 8, characterized in that: The mass ratio of the stearic acid, microcrystalline wax, PE wax and monoglyceride is 1-3:0.1-1:0.1-2:2-3.
10. The UPVC material with high rigidity and high impact resistance according to claim 1, characterized in that: The composition of the UPVC material with high rigidity and high impact resistance is as follows in terms of mass fractions: The weight of PVC resin is 100 parts, ABS resin 10 parts, MBS resin 10 parts, calcium carbonate 140 parts, heat stabilizer 8 parts, processing aid 10 parts, lubricant 2 parts, titanium dioxide 1.15 parts; The calcium carbonate is light activated calcium carbonate; the heat stabilizer is a composite calcium zinc stabilizer; the processing aid is an ACR processing aid; and the lubricant is 1 part of stearic acid and 1 part of PE wax.
11. The method for preparing the UPVC material with high rigidity and high impact resistance according to any one of claims 1 to 10, characterized in that: The steps include: Step 1: Weigh each component raw material as required; Step 2: Add the raw materials of each component into the mixer, heat it up, then cool it and discharge it; Step 3: The mixed material obtained in step 2 is processed and formed by extrusion process.
12. The preparation method according to claim 11, characterized in that: In the step 2, the temperature is raised to 120-150° C. and then cooled down; when cooled to 20-60° C., the material is discharged.
13. The preparation method according to claim 11, characterized in that: In step 3, the extrusion process is carried out using a twin-screw extrusion process, and the specific process includes the following steps: Step 3-1: The extrusion device controls the temperature to 100-130°C and maintains the preheating temperature; Step 3-2: Heat the barrel to 150-230°C, adjust the parameters, extrude the raw material mixture, and pull it into shape.
14. The preparation method according to claim 13, characterized in that: In step 3-1, the preheating temperature is maintained for 30-120 minutes.
15. The preparation method according to claim 13, characterized in that: In step three-2, the parameters are controlled as follows: the current is controlled at 10A-30A, the extrusion speed is controlled at 5-20r / min, the feeding speed is controlled at 5-20 r / min, the main machine vacuum is controlled below -0.02MPa, and the mold temperature is controlled at 150-230°C.
16. The preparation method according to claim 13, characterized in that: In the step 3-2, in the traction molding section, the traction speed is controlled at 0.5-1.5 m / s, and the molding vacuum is controlled below -0.02 MPa.
17. Use of the UPVC material with high rigidity and high impact resistance according to any one of claims 1 to 10 in the field of electrical engineering.
18. The use according to claim 17, characterized in that: The UPVC material with high rigidity and high impact resistance is used in polymer cable trays.
Citation Information
Patent Citations
Shock resistant modified polyvinyl chloride cable sheath material
CN104194229A
Antistatic flame-retardant composite material for coal mines and preparation method of antistatic flame-retardant composite material
CN104292699A
Rigidity improving method suitable for high-filling PVC (polyvinyl chloride) material
CN114316470A